2003
DOI: 10.1155/s1463924603000038
|View full text |Cite
|
Sign up to set email alerts
|

CTAD as a universal anticoagulant

Abstract: The feasibility of CTAD (a mixture of citrate, theophylline, adenosine and dipyridamole) as a new anticoagulant for medical laboratory use was studied prospectively. Whole blood anticoagulated with CTAD exhibited results very similar to those of blood anticoagulated with EDTA on complete blood count and automated white cell differential except for a slight decrease in platelet count and mean platelet volume. Chemistry test data for plasma obtained from CTAD whole blood were close to those obtained for matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Human biochemistry profiles showed that similar values were obtained in sera and CTAD plasmas for total proteins, albumin, total bilirubin, urea, creatinine, AST, ALT, CK, glucose and potassium, whereas the values for Na and Cl differed notably, 1 which is consistent with the input of Na ions derived from the sodium citrate in the CTAD solution. In this study, biochemistry results obtained in CTAD were compared with heparin plasma and not to serum, because it is the specimen used in our institution.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Human biochemistry profiles showed that similar values were obtained in sera and CTAD plasmas for total proteins, albumin, total bilirubin, urea, creatinine, AST, ALT, CK, glucose and potassium, whereas the values for Na and Cl differed notably, 1 which is consistent with the input of Na ions derived from the sodium citrate in the CTAD solution. In this study, biochemistry results obtained in CTAD were compared with heparin plasma and not to serum, because it is the specimen used in our institution.…”
Section: Discussionsupporting
confidence: 67%
“…In human medicine, PT, APTT and fibrinogen measurements in citrate and CTAD plasmas were very similar and highly correlated (r >0.92). 1 In our study, plasma coagulation test results for PT, APTT, fibrinogen and AT were usually close, even though they were sometimes statistically different. Very few clinical misclassifications were observed for PT and AT.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In practice, this study is difficult to conduct, and the GFHC co-opts the current 10% factor and recommends caution if the sample is analyzed more than three hours after sampling. The CTAD mixture is another commonly used EDTA-alternative, and several studies have shown that this anticoagulant is a good solution when dealing with platelet clumping with EDTA [59][60][61]. The long-term stability of the platelet count is better, but the problem of dilution persists, not mentioning the increased cost.…”
Section: Alternatives To Edtamentioning
confidence: 99%
“…A preliminary study in humans 19 showed that CTAD (citrate–theophylline–adenosine–dipyridamole) specimens gave similar results to EDTA specimens for the complete blood cell count (CBC), close to citrate specimens for secondary hemostasis variables (i.e., prothrombin time [PT], activated partial thromboplastin time [APTT], and fibrinogen), and close to plasma specimens for many biochemistry variables (i.e., total proteins, albumin, total bilirubin, urea, creatinine, aspartate aminotransferase [AST], alanine aminotransferase [ALT], creatine kinase [CK], glucose, and potassium), whereas the values for Na and Cl differed notably; both showed unacceptable biases because of the presence of sodium in CTAD and because testing for divalent cations was prevented by the formation of citrate salts. Moreover, CTAD has been shown to be a good substitute for EDTA in feline hematology as it limits platelet clumping and thus provides a more accurate platelet count.…”
mentioning
confidence: 99%